2015
DOI: 10.1556/030.62.2015.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell, the peculiar member of the immune system: A homeostatic aspect

Abstract: The mast cell is a member of the immune system having a basic role in allergic (anaphylactic) reactions. However, it contains, synthesizes, stores and secretes lots of substances, which initiates other reactions or participates in them. These are in connection with the deterioration of tissue correlation, as malignant tumors, angiogenesis, wound healing, pregnancy and different pathological conditions. In addition - as other members of the immune system - mast cells can synthesize, store and secrete hormones c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 167 publications
(156 reference statements)
0
6
0
Order By: Relevance
“…Many studies have shown that MCs are crucial for the maintenance of tissue function, tissue homeostasis, and during all steps of tissue repair from the initial inflammatory reaction and proliferation of connective cellular elements to final remodelling of the extracellular matrix [ 6 , 7 ]. However, some effects of MCs are controversial and frequently opposite most likely due to the phenotypic heterogeneity of MCs in different tissues [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that MCs are crucial for the maintenance of tissue function, tissue homeostasis, and during all steps of tissue repair from the initial inflammatory reaction and proliferation of connective cellular elements to final remodelling of the extracellular matrix [ 6 , 7 ]. However, some effects of MCs are controversial and frequently opposite most likely due to the phenotypic heterogeneity of MCs in different tissues [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCs are very special cells of the immune system derived from pluripotent cells of the myeloid lineage and are widely distributed in connective tissues throughout the body, including the reproductive system and placental tissue of women [ 4 6 ]. Unlike other white blood cells, MCs present in blood are immature in the form of MC progenitors generated from CD34 + hematopoietic stem cells, and these cells become fully competent after recruitment into the tissue at target localization [ 7 ]. Terminal differentiation of MCs occurs under the influence of c-kit ligand (CD117) and cytokine stem cell factor (SCF) in the local site microenvironment containing other distinct cytokines (e.g., IL-3 and IL-33), especially growth factors [ 8 ].…”
Section: Mcs and Mc-derived Mediators In A Woman's Reproductive Syste...mentioning
confidence: 99%
“…Unlike other white blood cells, MCs present in blood are immature in the form of MC progenitors generated from CD34 + hematopoietic stem cells, and these cells become fully competent after recruitment into the tissue at target localization [7]. Terminal differentiation of MCs occurs under the influence of c-kit ligand (CD117) and cytokine stem cell factor (SCF) in the local site microenvironment containing other distinct cytokines (e.g., IL-3 and IL-33), especially growth factors [8].…”
Section: Mcs and Mc-derived Mediators In Amentioning
confidence: 99%
“…Mast cells are specialized bone marrow-derived cells that play an important role in health [1] and in allergies [2][3][4][5][6][7][8][9][10][11][12] but also in innate and in adaptive immune processes [13][14][15][16], antigen presentation [16,17], regulation of T-cell responses [18][19][20], autoimmunity [21] and inflammation [10,[22][23][24][25] in response to allergic and immunologic stress [4,26,27] but also non-allergic stress and toxic stimuli [10,28]. Mast cells are increased in number and are more reactive in mastocytosis [26] and mast cell activation syndrome (MCAS) [26,29,30], but they can also participate in other disorders [4,10,[31][32][33], including neurotrauma, neuroinflammatory and neurodegenerative diseases [34][35][36].…”
Section: Introductionmentioning
confidence: 99%